“Behind Every Successful Woman is a Tribe of Other Successful Women” – A Preliminary Corpus-Assisted Study of Evaluative Adjectives in Women Entrepreneurs’ Blogs - Fronczak, Katarzyna (Research in Language, 2025)
Women entrepreneurs’ blogs represent a unique and evolving form of digital discourse, blending professional authority with personal engagement. Within this genre, evaluative language plays a crucial role in shaping credibility, persuasion, and identity. While evaluative adjectives have been widely studied in formal and academic contexts, their opinion-forming function in entrepreneurial communication remains largely unexplored. This study investigates how opinions and evaluations are constructed through the use of evaluative adjectives in women entrepreneurs’ blogs, examining their distribution, rhetorical function, and impact on audience engagement. Using a corpus-assisted methodology, the analysis is conducted on the lexical data extracted from the Women Entrepreneurs Blog Corpus (WEBC), a dataset of 329,896 words from 318 blog posts. The study identifies evaluative adjectives through frequency-based corpus analysis and categorises them into distinct semantic groups, which serve as the foundation for examining how women entrepreneurs use linguistic choices to construct stance, authority, and persuasion in digital business communication. A quantitative analysis of categorised evaluative adjectives reveals that positive-polarity evaluative adjectives are the most frequent, reinforcing optimism and motivation. Adjectives of importance follow, emphasising authority and expertise, while size- and time-related adjectives occur moderately, highlighting growth and progress. Attitude and emotion adjectives appear less frequently, contributing to a confident and engaging tone. Negatively-charged adjectives are rare and often reframed, whereas certainty and likelihood adjectives are the least frequent, reflecting a preference for flexibility over absolutes in entrepreneurial discourse. By situating this analysis within the broader framework of stance and evaluation in specialised discourse, this study provides insights into how women entrepreneurs use language to formulate and express opinions, navigate professional identity, establish credibility, and engage their audiences. The research contributes to discussions on opinion expression in digital business communication, shedding light on the intersection of gender, entrepreneurship, and linguistic strategies in online discourse.